Microbial Extracellular Polymeric Substance: A Pioneer in Ensuring Soil Health and Sustainable Development of Agriculture - Sixuan He; Yingjie Zhao; Xiaoqing Guo; Yuanhang Yu; Jingyi Sui; Shao-Hua Chen; Ye Yang; Wenping Zhang (Journal of Agricultural and Food Chemistry, 2026)
Abstract Microbial extracellular polymeric substances (EPS) refer to complexes of polysaccharides, proteins, and nucleic acids secreted by microorganisms, which perform diverse functions in soil ecosystems. This Review elucidates the mechanisms of EPS action at three levels: cytoprotection, soil improvement, and pollution remediation. At the cellular level, EPS maintain cellular integrity and mitigate stress through the formation of biofilm barriers and chelation by its functional groups. At the soil level, EPS improve the aggregate structure and water retention capacity and stabilize heavy metals. For remediation, EPS adsorb and remove pollutants, extending its functionality from cellular protection to that of environmental remediation. EPS have wide-ranging application prospects; however, cost reduction and mechanism elucidation remain as challenges. Future green applications will need to be propelled by advances in synthetic biology and materials science.